Comparative Study of Energy Efficiency Test Methods and Energy Efficiency Limit Values of Water Chiller (Heat Pump) Units - Tao Yiwei; Liu Jian; Li Mingxia; Cheng Jianhong; Gao Yifeng; Fang Yuan; Zhang Xiaosong (Zhileng xuebao)
As the main energy-consuming equipment of the centralized air-conditioning system, the improvement of the energy efficiency of water chiller (heat pump) units has a significant role in promoting the realization of the "dual carbon" target. GB/T 18430, as a basic standard for plumbing units, is nearing the end of its revision, and the accompanying energy efficiency standards GB19577–2015 need to be revised and upgraded accordingly. In this study, the assessment method of comfort-type water chiller (heat pump) units in GB/T 18430 is analyzed and compared with those of the corresponding U.S. and European standards. A theoretical model of water-cooled water chiller (heat pump) units is constructed such that the limited value levels specified in the energy efficiency standards of China, the U.S., and Europe are converted into the same index for comparison. The IPLV entry limit values of China's water-cooled units, after increases of 5.4% and 25.2%, can match the energy efficiency levels of Path A and Path B of the American standard, respectively, and align with the European standards after a 13.4% increase; the energy efficiency limit values of air-cooled units can be basically on par with the European energy efficiency standards after increasing by 25.4%. This work provides a reference for the subsequent revision of the energy efficiency standard GB19577—2015.